Assessment of geothermal power potential in Buyuk Menderes Basin, Turkey - Yamanlar, Şenol; Korkmaz Başel, Emine Didem; Serpen, Ümran (Elsevier, 2020)
Turkey’s installed geothermal capacity for power generation as of December 2019 is 1500 MWe. Most of this installed capacity is generated by the power plants located in the Buyuk Menderes graben. Geologically Buyuk Menderes graben is a huge structure having several discovered geothermal resources and can be considered as a geothermal basin. The aim of this study is to estimate the geothermal power potential of Buyuk Menderes graben. To achieve this object, a stochastic methodology, which is used to evaluate hydrocarbon-bearing basins, is adapted from the oil and natural gas industry. This methodology provides a way to quantify the geothermal potential in a range of possible values by evaluating the individual fields in the basin using stored heat technique. A total of 34 (21 proven and 13 probable occurrences) geothermal fields having medium to high temperature (T ≥ 100 °C) values are evaluated using the Monte Carlo Simulation technique. In these simulations, available geological, geochemical, geophysical data are used along with the data obtained from the drilled wells in the region. The power potential (MWe) values for 21 proven fields in terms of P10, P50 and P90 values are determined to be 888, 1077 and 1311 MWe, respectively. Considering the 13 probable occurrences along with the proven fields, the lower and upper limits of the total power potential (P10 and P90) are 1156 and 1580 MWe, respectively. Moreover, the power potentials are also evaluated under the presence of uncertainty. By assigning 5/13, 6/13, and 7/13 probability values for the 13 probable occurrences, overall geothermal power potential P10 values are estimated as 1041, 1075, and 1101 MWe, respectively.
Keywords: geothermal resources; jeotermal kaynaklar; geothermal engineering; jeotermal mühendisliği; power resources; güç kaynakları; Buyuk Menderes graben; Büyük Menderes grabeni; Turkey; Türkiye